Response of China's Terrestrial Carbon Uptake to Shift in Nitrogen Deposition - L. Zhang; P. Li; G. Yu; H. He; Y. Jia; J. Zhu; W. Ju; C. Zhang; X. Ren; T. Wang; Y. Zheng; H. WU (Earth's Future, 2025)
Abstract China has experienced a shift in nitrogen (N) deposition from an upward trend since 1980s to stabilized since 2001–2005 and decline in recent years due to N management. Global atmospheric chemical transport models tend to underestimate the magnitude of N deposition in China and fail to reproduce such a shift. How do underestimation and trend shift in N deposition influence China's terrestrial carbon (C) uptake remains unclear. Here we used a new N deposition data set and three independent methods to investigate the effect of N deposition on terrestrial C uptake in China. We found that the magnitude and trend of China's terrestrial C sink induced by N deposition (∆CNdep) would be underestimated during 1990–2015 when using commonly used global atmospheric N deposition data sets. Despite the decrease in N deposition trend, the increasing rate of ∆CNdep changed from 4.42 Tg C yr−2 in 1990–2005 to 5.64 Tg C yr−2 in 2006–2015, which was dominated by subtropical and tropical monsoon region. The interactive effect of N deposition with other environmental factors has a greater impact on the trend of ∆CNdep than direct effect. Our results highlight the rising terrestrial C uptake as N deposition stabilizes and the crucial role of interaction mechanisms among global change factors in assessing the impact of declining reactive N inputs on China's future land C sinks under C neutrality targets.